Moral values and their role in the standards of conduct of state and municipal employees - Oleg Zabuzov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2016)
The article briefly traces the transformation of values of the Russians. Given the author's analysis of the concepts of «values», «moral values of employees». Offered their own interpretation of these concepts. The investigated structural components of the system of moral values of professionals and managers. Highlighted a number of factors influencing the development of moral values of managers.